Agglomerations of The Stavropol Region: Comparison of Spatial and Demographic Dynamics - V. M. Eshrokov; A. A. Cherkasov; N. V. Sopnev (Наука. Инновации. Технологии)
Introduction. Two agglomeration-type settlement systems have formed in the Stavropol Krai, – the monocentric Stavropol agglomeration and the polycentric agglomeration of the Caucasian Mineral Waters (the CMW). At the present stage, demographic processes in the Stavropol Krai most intensively occur within the “borders” of the represented agglomerations; migration processes are observed leading to the population being drawn into the centers of agglomerations, which increases their role in the settlement system.The purpose of this study is to compare the spatial and demographic dynamics of agglomerations in the Stavropol Krai, highlighting common features in demographic processes and features characteristic of each agglomeration.Materials and research methods. The work uses data from the Office of the Federal State Statistics Service for the Stavropol Territory (from 2012 to 2021), population census materials (1989, 2002, 2010, 2021), documents from territorial planning and urban planning, our own observations and field results territory research. Based on these data, a general description of the Stavropol agglomeration and the CMW agglomeration is given, spatial organization of settlement is analyzed, and current trends in its demographic development are determined.Research results and their discussion. In the course of the study, the authors analyze the birth rate, mortality, natural population growth, migration processes, population dynamics, and the ethnic composition of the population of each agglomeration of the Stavropol Territory. The analysis was carried out at the level of cities, urban and municipal districts, which makes it possible to assess intra-agglomeration processes, whether they are uniform for the entire agglomeration or have spatial patterns.Conclusions. The analysis of demographic dynamics of two agglomerations of the Stavropol Krai allows the authors to draw conclusions. The Stavropol agglomeration and the agglomeration of the Caucasian Mineral Waters act as centers of concentration of the urban population in the Stavropol region and are the main areas of attraction for migrants. Agglomerations are characterized by increasing numbers and natural population growth. Migration population growth, which is currently declining, has contributed to an increase in population throughout the post-Soviet period. Currently, agglomerations have concentrated the significant demographic potential of the Stavropol region.